A Review on The impact of Transistor Configuration as an amplifier - Aithekar, Vijay (International Journal of Advanced Science Computing and Engineering, 2021)
In the electronic era, the development of the transistor is unquestionably one of the most valuable contributions in the field of Electronic components. Transistor has an application to work as a switch and as an amplifier and almost in all cases. The transistor is taken as the use of an amplifier because it gives proper biasing. In this review paper, we are going to compare the Transistor as an amplifier with three configurations and select one desirable configuration with perfect amplification & that is CE configuration and taken as used in everywhere mostly.